Disparities in Perspectives of Justice Across Adversarial Lines. - Soultanian, Ani E. (Tufts Archival Research Center, 2018)
Based on this mixed methods approach, we found that the attorneys’ views were largely consistent with their respective institutional perspectives, although the adversaries share more commonalities than we would have thought. These oppositional attitudes towards the criminal justice system, then, manifested as varying definition of what is just and what is fair for defendants and victims, respectively. After embarking on this project, I have learned how the very format of the criminal justice process, which immediately separates the adversaries and their respective parties, yields stark ideological differences that inform every step of this process. Overall, the results of the project suggest that different positionalities and the subsequent, disparate theories of justice, as well as various forms of bias, yield problematic consequences that perpetuate structural violence and mass incarceration. The criticisms that the adversaries shared further assert that the adversarial trial system is a failing relic that no longer serves the needs of the public. However, our results also indicate that reform efforts will be painfully slow unless prosecutors and defense attorneys both step into the aisle and create a coalition for structural changes toward restorative practices. Although this idea may currently seem utopian at best, future studies may garner the momentum needed to spark this drastic change.